1997
DOI: 10.1046/j.1365-3040.1997.d01-10.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elevated CO2 and temperature on photosynthesis and Rubisco in rice and soybean

Abstract: Rice (Oryza sativa L. cv. IR-72) and soybean (Glycine max L. Merr. cv. Bragg), which have been reported to differ in acclimation to elevated CO2, were grown for a season in snnlight at ambient and twice-ambient [CO2], and under daytime temperature regimes ranging from 28 to 40 °C. The objectives of the study were to test whether CO2 enrichment could compensate for adverse effects of high growth temperatures on photosynthesis, and whether these two C3 species differed in this regard. Leaf photosynthetic assimil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
94
1
7

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(114 citation statements)
references
References 33 publications
12
94
1
7
Order By: Relevance
“…The results of some studies have suggested that increasing [CO 2 ] will result in increased photosynthesis (Kimball et al, 2002;Vu et al, 1997;Yang et al, 2006). Several recent studies have shown that photosynthesis of C 3 plants increases by 30-50% with doubled [CO 2 ] (Ainsworth & Rogers, 2007;Baker et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The results of some studies have suggested that increasing [CO 2 ] will result in increased photosynthesis (Kimball et al, 2002;Vu et al, 1997;Yang et al, 2006). Several recent studies have shown that photosynthesis of C 3 plants increases by 30-50% with doubled [CO 2 ] (Ainsworth & Rogers, 2007;Baker et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In this study region, increasing temperature in the near and distant future may not often reach the level for heat stress on photosynthesis for which the cardinal temperature is above 32 °C for soybean (Hatfield et al 2011;Vu et al 1997). Therefore the soybean response to increasing temperature will depend on current local mean temperature (Boote 2011).…”
Section: Response To Climate Changementioning
confidence: 96%
“…Simulations by different crop models provide useful information for assessing the uncertainties in the projected crop production associated with the uncertainties in greenhouse gas emission scenarios and climate projections (Long et al 2006;Reich et al 2006;Rogers et al 1995;Twine Vu et al 1997). It is understandable that a crop model may be good in mimicking some, but not all, aspects of the cropping system.…”
Section: Response To Climate Changementioning
confidence: 99%
“…Plantas com metabolismo C3 são mais beneficiadas pelo aumento da concentração de CO 2 atmosférico do que plantas com metabolismo C4 (TUBIELLO et al, 2000;SIQUEIRA et al, 2001;STRECK, 2005). No entanto, se o aumento da concentração de CO 2 for acompanhado de aumento da temperatura do ar, poderá não haver aumento no crescimento e produtividade das culturas devido ao encurtamento do ciclo (WIEGAND e CUELLAR, 1981;SIONIT et al, 1987;HUNT et al, 1991;BUTTERFIELD e MORISON, 1992;SHAYKEWICH, 1995, SIQUEIRA et al, 2001) e aumento da respiração (fotorespiração e fase escura da respiração) (ROSENBERG et al, 1983;LONG, 1991;VU et al, 1997;TAIZ e ZEIGER, 2004). Portanto, em estudos de impactos das mudanças climáticas sobre os agroecossistemas, devese dar especial atenção ao efeito do aumento de temperatura (aquecimento global) no desenvolvimento vegetal e assim caracterizar mudanças no ciclo das culturas em diferentes cenários meteorológicos.…”
Section: Introductionunclassified